PENGARUH DANA OTONOMI KHUSUS DAN DANA ALOKASI KHUSUS TERHADAP ALOKASI BELANJA KESEHATAN PADA DINAS KESEHATAN ACEH BARAT - Winni Irmiana; Ika Rahmadani (IAIN Lhokseumawe, 2022)
Aceh Barat is one of the regions receiving special autonomy funds and special allocation funds, but there are still many shortages of health facilities in the Aceh Barat region, even though health is the most important thing in human life. The purpose of this study is to see the effect of special autonomy funds and special allocation funds on the allocation of health spending at the Aceh Barat Health Office. This research is a quantitative type. In this research study, the data used is secondary data in the form of the Financial Statements of the West Aceh Health Service for 2010-2021. This data is time series data, to collect this data the researcher uses financial report documentation techniques obtained directly from the West Aceh Health Office. This study uses multiple linear regression test. The technique in this study uses the classical assumption test, multiple linear regression, t test and f test. From the test results, it was found that the Special Autonomy Fund did not have a significant partial effect on the allocation of health spending where the t value was 0.2945 > 0.05 and DAK had a significant effect on the partial health expenditure allocation where the t value was 0.0004 < 0, 05 , while simultaneously these two variables have a significant influence on the allocation of health spending where the f value is 0.000247 < 0.05. Keywords: Health Expenditure Allocation, Special Autonomy Fund and Special allocation fund